REACTIVE CHANGES IN THE VESSELS OF THE RAT’S CAECUM WALL MUCOSA AND SUBMUCOUS MEMBRANE IN RESPONSE TO THE EFFECT OF COMPLEX FOOD ADDITIVES - Kinash, O.V.; Yeroshenko, G.A.; Shevchenko, K.V.; Perederii, N.A.; Riabushko, O.B.; Onipko, V.V.; Peredera, R.V. (World of Medicine and Biology, 2024)
The aim of the work was to determine the dynamics of changes in the metric parameters of the vessels of the mucous membrane of the wall of the cecum and the submucosa of rats in response to the action of complex food additives. The study was conducted on 84 sexually mature male rats. Rats of the control group were orally injected with physiological saline. Rats of the experimental group were orally administered 0.6 mg/kg of sodium nitrite, 20 mg/kg of monosodium glutamate, and 5 mg/kg of Ponceau 4R in 0.5 ml of distilled water once a day. The selection of samples for histological examination was carried out at 1, 4, 8, 12 and 16 weeks. It turned out that the use of food additives in a complex leads to a structural reorganization of the vessels of the mucous membrane and submucosa of the cecum of rats.
Keywords: food additives; monosodium glutamate; sodium nitrite; ponceau 4R; rat